Boosting the stability of lead halide perovskite nanocrystals by metal–organic frameworks and their applications. Issue 32 (9th August 2022) - Shankar, Hari; Ghosh, Sukanya; Kar, Prasenjit
Abstract : An overview of recent development on stability improvement and various applications of lead halide perovskite nanocrystals by metal organic frameworks. Abstract : Lead halide perovskites (LHPs) have demonstrated their expertise in the field of optoelectronics. However, the commercialization of these materials is not easy because they have poor stability in humidity, light, and heat. This review provides a brief discussion regarding the decomposition of perovskite NCs through intrinsic and extrinsic environmental factors, including explaining their degradation mechanism. Various strategies have been adopted, focusing on improving the stability of perovskites. It also calls attention to the literature about stability-enhancing approaches. In this recent field, researchers have tried to a great extent to overcome the obstacle of environmental instability and materialistic applications of perovskite by engaging the perovskite NCs inside the matrix of porous-MOFs. The purpose of this review is to provide an up-to-date literature survey about the blooming new properties and stability improvement in perovskites by loading the porous metal–organic frameworks (MOFs), including the different synthesis approaches that have been developed. Moreover, the chemistry of different MOFs' capability to control the shape, size, and optical properties of resulting perovskite NCs has also been discussed in this perspective. Finally, we concluded the encapsulation strategy of perovskite NCs inside the MOFs had given revolutionary results to improve the stability of perovskite NCs and their new potential application.